Inovasi Pengelolaan UMKM dalam Peningkatan Kesejahteraan Masyarakat Kota Semarang - Setyaningsih, Sri; Satyarini, Marhaeni Dwi (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora; Vol 1 No 1 (2023): Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
UMKM in the city of Semarang have a great potential to be developed because of the broad market, raw materials that are easily obtained and large human resources are the supporting variables of the development of the MSME, but it needs to be observed several things in line with the development of small small businesses. The type of research is descriptive with literature study. The aim is to get a theoretical foundation regarding the problems studied and also give a clear picture to the reader. Library Research (Library Research) is a literature search that is not only for the first step in preparing the research framework but at the same time utilizes library sources to obtain research data, be it bibliographic tools, such as reference books, bulletin index references and magazines, newspaper and tabloid indexes, document indexes, manuscript indexes, and other sources. Analysis of this research data is qualitative, which focuses on systematic explanations about the facts obtained by research activities. Activities in qualitative data analysis are carried out interactively and takes place continuously until saturated. Data analysis techniques include 3 (three) components, namely: 1) data reduction, 2) data presentation, and 3) withdrawing conclusions and verification. The results obtained conclusions that the development of innovation in the management of MSMEs in Semarang City contributes to the positive improvement of the community with various criteria and its classification. Therefore needed management innovations, such as: business development must be followed by good management, good planning and minimizing failures, mastery of knowledge that supports business sustainability, managing an efficient and effective production system, as well as making a breakthrough and innovation that makes the difference from Competitors, as a step towards success in managing the UMKM.